A Critical Pragmatic Analytical Framework of Sectarian Discourse - Hussam Aldeen Nidhal Hadi; Basim Jubair Kadhim (Randwick International of Education and Linguistics Science Journal, 2023)
This paper is concerned with developing a model of analysis of sectarianism in terms of critical pragmatics. It aims to introduce a critical pragmatic approach to the sectarian discourse. Based on critical discourse analysis of relevant approaches, pragmatic notions and domains, critical pragmatic analyses and linguistic realizations of sectarianism as a social practice within the speech event of preaching, the model is structured and introduced. Certain observations and comments on the models are raised as a matter of setting an adequate model for the analysis of sectarian discourse under critical pragmatics. Using the model, the paper has come up with certain conclusions such as that pragmatics plays a key role in manifesting and uncovering sectarian discourse as a hidden ideology, and that sectarianism is revealed by preachers only through critical pragmatic strategies, for which the present approach can be f use to de-sectarianize such discourse.